2020
DOI: 10.3389/fendo.2019.00924
|View full text |Cite
|
Sign up to set email alerts
|

Management of Osteogenesis Imperfecta

Abstract: Osteogenesis imperfecta (OI) is the term used to describe a group of rare inherited skeletal disorders characterized by a greatly increased risk of fragility fractures (1). Mutations in several genes can cause OI but the condition is most commonly caused by mutations of COLIA1 or COL1A2 resulting in the production of collagen which is abnormal or present in reduced amounts. Fractures in OI are particularly common during childhood but the elevated fracture risk continues throughout life. Bone mineral density (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 69 publications
1
73
0
4
Order By: Relevance
“…Randomized controlled trials of bisphosphonates in OI have consistently shown that BMD is increased, but the effects of bisphosphonates on fracture rate are uncertain (11). As to our patient, he had no more fractures after 6 years' administration of bisphosphonate, and his bone density increased, his Z-score was above −2.0; meanwhile, considering the drug holiday of bisphosphonates, we didn't administrate bisphosphonates at the latest admission.…”
Section: Discussionmentioning
confidence: 68%
“…Randomized controlled trials of bisphosphonates in OI have consistently shown that BMD is increased, but the effects of bisphosphonates on fracture rate are uncertain (11). As to our patient, he had no more fractures after 6 years' administration of bisphosphonate, and his bone density increased, his Z-score was above −2.0; meanwhile, considering the drug holiday of bisphosphonates, we didn't administrate bisphosphonates at the latest admission.…”
Section: Discussionmentioning
confidence: 68%
“…Notably, RANKL promotes osteoclast differentiation (see Section 2.4 ). At present, denosumab, a monoclonal antibody against RANKL, which inhibits osteoclastic activity, is being tested in clinical trials in OI patients [ 42 ].…”
Section: Genetic Causes Of Bone Fragilitymentioning
confidence: 99%
“…Bisphosphonates are commonly used. These drugs 189 have anti-resorptive properties which inhibit the function of osteoclasts (Ralston and Gaston, 2020) . Treatment with cyclical intravenous pamidronate, a second-generation bisphosphonate, has shown better results in children.…”
Section: Medical Managementmentioning
confidence: 99%
“…However, the death rate may be higher than expected in children as they are prone to infection due to low immunity (Fauci et al, 2020). The best treatment practice is multi-disciplinary approach (Mueller et al, 2018;Ralston and Gaston, 2020). This review aims to identify the potential effects of the multidisciplinary approach in patients with orthopaedic conditions.…”
Section: Introductionmentioning
confidence: 99%